Organic electrode for non-aqueous potassium-ion batteries. (November 2015) - Chen, Yanan; Luo, Wei; Carter, Marcus; Zhou, Lihui; Dai, Jiaqi; Fu, Kun; Lacey, Steven; Li, Tian; Wan, Jiayu; Han, Xiaogang; Bao, Yanping; Hu, Liangbing
Abstract: Potassium-ion (K-ion) batteries can be an attractive alternative for grid-scale energy storage due to the abundance of K resources. For the first time, we designed and fabricated a non-aqueous K-ion battery (KIB) by employing 3, 4, 9, 10-perylene–tetracarboxylicacid–dianhydride (PTCDA) as the cathode. The PTCDA electrode exhibits a high capacity of 131 mA h g −1 in the potential range of 1.5–3.5 V vs. K/K +, which corresponds to the insertion of two K ions per PTCDA molecule. The PTCDA cathode also shows great cycling performance, with a capacity retention of 66.1% over 200 cycles. Furthermore, K11 PTCDA can be obtained when discharging PTCDA to 0.01 V vs. K/K +, which delivers a high capacity of 753 mA h g −1 . The excellent electrochemical performance makes PTCDA a promising organic electrode based on K-ion chemistry for grid-scale energy storage. Graphical abstract: Highlights: For the first time, we designed and fabricated a non-aqueous potassium-ion batteries (KIBs) by PTCDA as the cathode. The PTCDA exhibits a high capacity of 131 mA h g −1 in the potential range of 1.5–3.5 V vs. K/K + . PTCDA shows great capacity retention of 66.1% over 200 cycles. K11 PTCDA can be obtained when discharging PTCDA to low voltage.